Analisis Modifikasi Filter Fuel Caterpillar C15 Di Pusat Listrik Laiwui - Muhammad Ridwan; Iwan Gunawan; Said Hi Abbas (CV. IRA PUBLISHING, 2023)
Today the development of technology is very rapid both in the field of basic science and the modification of a tool and even modifications in the field of engines, both combustion engines and electric engines. Modifications are needed to improve the performance of a machine. Modifications that can be applied to diesel engines that use fuels such as MFO, diesel, and biosolar. Diesel oil is the result of distillation of petroleum which is used only as fuel for compression ignition engines used by injectors. Biodiesel or biosolar is a type of fuel made from vegetable oil. The main objective of developing biodiesel is to substitute fossil fuels to produce green, environmentally friendly energy. The research we conducted was on the Caterpilar C15 Engine at PLTD Laiwui, and used biodiesel fuel (B30). Data collection is carried out when the machine is operating normally. From the data, we process it by analyzing it so we can find the main problem. From the results of the analysis, we get the root of the problem, namely the engine often shuts down because the pressure drops in the fuel system, this is caused by a dirty filter. From the results of the analysis, the researchers made a plan to modify the fuel system on the Caterpilar C15 engine at PLTD Laiwui. The modification applied is to add a material filter before entering the machine. then a performance test was carried out for 1 week and the modified data was compared with the initial data before the modification.